PENGARUH PENGETAHUAN AKUNTANSI DAN JIWA KEWIRAUSAHAAN TERHADAP PENGGUNAAN INFORMASI AKUNTANSI DALAM PEMBUATAN KEPUTUSAN INVESTASI - Krisanti, Putu Rina (E-Jurnal Akuntansi, 2012)
Accounting information is the information needed by an entrepreneur to make investment decisions. High entrepreneurial spirit that would make someone want to continue to develop the business wich has been owned, one way to expand an existing business is by investing. But today many entrepreneurs who do not have good accounting knowledge, many entrepreneurs do not keep records of transaction on their efforts so there is no financial information is generated to make investment decision. This study aims to investigate the positive and significant relationship between knowledge of accounting and entrepreneurial spirit to the use of accounting information in making investment decision. The data analysis technique used in this study were multiple linear regression analysis techniques. The result of this study indicate that the accounting knowledge and entrepreneurial spirit influential significant and positive effect on the use of accounting information in making investment decisions.   Key Words : accounting knowledge, entrepreneurial spirit, accounting information, investment